Intracranial approach for sub-second monitoring of neurotransmitters during DBS electrode implantation does not increase infection rate. - Brittany Liebenow; Michelle Williams; Thomas Wilson; Ihtsham Ul Haq; Mustafa S Siddiqui; Adrian W Laxton; Stephen B Tatter; Kenneth T Kishida (PLoS ONE, 2022)
Introduction Currently, sub-second monitoring of neurotransmitter release in humans can only be performed during standard of care invasive procedures like DBS electrode implantation. The procedure requires acute insertion of a research probe and additional time in surgery, which may increase infection risk. We sought to determine the impact of our research procedure, particularly the extended time in surgery, on infection risk. Methods We screened 602 patients who had one or more procedure codes documented for DBS electrode implantation, generator placement, programming, or revision for any reason performed at Wake Forest Baptist Medical Center between January 2011 through October 2020 using International Classification of Diseases (ICD) codes for infection. During this period, 116 patients included an IRB approved 30-minute research protocol, during the Phase 1 DBS electrode implantation surgery, to monitor sub-second neurotransmitter release. We used Fisher's Exact test (FET) to determine if there was a significant change in the infection rate following DBS electrode implantation procedures that included, versus those that did not include, the neurotransmitter monitoring research protocol. Results Within 30-days following DBS electrode implantation, infection was observed in 1 (0.21%) out of 486 patients that did not participate in the research procedure and 2 (1.72%) of the 116 patients that did participate in the research procedure. Notably, all types of infection observed were typical of those expected for DBS electrode implantation. Conclusion Infection rates are not statistically different across research and non-research groups within 30-days following the research procedure (1.72% vs. 0.21%; p = 0.0966, FET). Our results demonstrate that the research procedures used for sub-second monitoring of neurotransmitter release in humans can be performed without increasing the rate of infection.